2017
DOI: 10.1136/bcr-2017-220218
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative gluteal compartment syndrome following microsurgical free-flap hand reconstruction: the importance of early recognition and treatment

Abstract: Compartment syndrome, a surgical emergency, is caused by an increase in pressure within a closed osseofascial space, often due to trauma. This causes a decrease in tissue perfusion and ultimately tissue necrosis and multiorgan failure if not treated in a timely fashion. Gluteal compartment syndrome is a rare variant and often caused by a period of immobilisation secondary to intoxication with alcohol or drugs or during long operations, typically in the supine position. We report on a case of gluteal compartmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 7 publications
(6 reference statements)
1
4
0
Order By: Relevance
“…Sarwar et al describe the case in which a patient presented with gluteal CS following microsurgery to the hand, which had never been documented. This lends itself as evidence for the pathophysiology behind prolonged periods of vessel compression and its association with gluteal CS [8]. Similar findings were present in a case of a 65-year old who had been reported unconscious after heroin use.…”
Section: Discussionsupporting
confidence: 70%
“…Sarwar et al describe the case in which a patient presented with gluteal CS following microsurgery to the hand, which had never been documented. This lends itself as evidence for the pathophysiology behind prolonged periods of vessel compression and its association with gluteal CS [8]. Similar findings were present in a case of a 65-year old who had been reported unconscious after heroin use.…”
Section: Discussionsupporting
confidence: 70%
“… BMI: body mass index; AAA: abdominal aortic aneurysm; BMI: body mass index; EVAR: endovascular aneurysm repair; NR: not reported. References: Benevides & Nochi Júnior (2006); Cameron-Gagné et al (2018); Chew et al (2009); Hau et al (2016); Keene et al (2010); Kumar et al (2007); Matta & Kelley (2014); Mohanty et al (2019); O’Leary et al (2010); Oates et al (2016); Osteen & Haque (2012); Pereira & Heath (2015); Polacek et al (2009); Pua et al (2005); Reisiger et al (2005); Rudolph et al (2011); Sarwar & Ting (2017); Somayaji et al (2005); Ting et al (2015); Viviani et al (2016). …”
Section: Discussionmentioning
confidence: 99%
“…Gluteal compartment syndrome is a rare condition that mainly occurs after trauma directly to the gluteal area or prolonged immobilization with pressure on the gluteal region after intoxication or prolonged surgery [ 2 4 , 10 , 11 ]. Acute pelvic trauma can cause gluteal compartment syndrome due to local swelling from the injury that compromises vascular structures within a closed fascial space [ 1 , 11 , 12 ]. Postoperative gluteal compartment syndrome can occur due to local surgical trauma where structures have been incised and manipulated leading to edema; however, most cases of postoperative gluteal compartment syndrome affect the non-operative anatomical site due to prolonged immobilization and pressure.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have found that major risk factors for gluteal compartment syndrome include obesity, prolonged operative time, and epidural anesthesia [ 3 , 11 , 18 ]. Our patient had a morbidly obese BMI of 42.…”
Section: Discussionmentioning
confidence: 99%